Functional Plasmonic Nanocircuits with Low Insertion and Propagation Losses - Kriesch, Arian; Burgos, Stanley P.; Ploss, Daniel; Pfeifer, Hannes; Atwater, Harry A.; Peschel, Ulf (Nano Letters, 2013)
We experimentally demonstrate plasmonic nanocircuits operating as subdiffraction directional couplers optically excited with high efficiency from free-space using optical Yagi-Uda style antennas at extgreekl0 = 1550 nm. The optical Yagi-Uda style antennas are designed to feed channel plasmon waveguides with high efficiency (45% in coupling, 60% total emission), narrow angular directivity (<40°), and low insertion loss. SPP channel waveguides exhibit propagation lengths as large as 34 extgreekmm with adiabatically tuned confinement and are integrated with ultracompact (5 × 10 extgreekmm2), highly dispersive directional couplers, which enable 30 dB discrimination over extgreekDl = 200 nm with only 0.3 dB device loss.
EAM Import::2019-03-14

Generation and subwavelength focusing of longitudinal magnetic fields in a metallized fiber tip - Ploss, Daniel; Kriesch, Arian; Pfeifer, Hannes; Banzer, Peter; Peschel, Ulf (Optics Express, 2014)
We demonstrate experimentally and numerically that in fiber tips as they are used in NSOMs azimuthally polarized electrical fields (|Eazi|2 / |Etot|2 ≈55% ± 5% for extgreekl0= 1550 nm), respectively subwavelength confined (FWHM ≈450 nm ≈ extgreekl0/3.5) magnetic fields, are generated for a certain tip aperture diameter (d = 1.4 extgreekmm). We attribute the generation of this field distribution in metal-coated fiber tips to symmetry breaking in the bend and subsequent plasmonic mode filtering in the truncated conical taper.
EAM Import::2019-03-13

Measuring the Kerr-nonlinearity of Ag in plasmonic nano-circuits - Kriesch, Arian; Pfeifer, Hannes; Burgos, Stanley P.; Ploss, Daniel; Banzer, Peter; Atwater, Harry A.; Peschel, Ulf (Nonlinear Optics 2013, 2013)
We observe nonlinear switching of ultrashort (600fs) laser pulses in subwavelength plasmonic nanocircuits. This allows us to experimentally determine the third-order nonlinear coefficient of silver.
EAM Import::2019-03-12